Book Review. Issue 1 (1st March 2022) - Unknown
Abstract : Nicole Brown (2021) Lived Experiences of Ableism in Academia: Strategies for Inclusion in Higher Education Bristol: Policy Press, 352 pp., ISBN: 978-1447354116